Subsidies for the coastal planning of the municipality of Jaguaruna, Santa Catarina (2018)
The unplanned occupation of the Coastal Zone has promoted the replacement of the original natural environment by the anthropic environment. This transformation generates conditions that unbalance the Environmental Diversity (abiotic and biotic natures) and prejudice the anthropic environment. This problem tends to continue and worsen in small municipalities; as is the case of municipality of Jaguaruna, Santa Catarina, Brazil. The present paper presents the method of structuring the irst steps of a coastal strategic plan developed in Camacho Balneary/Jaguaruna through actions and scenarios of management based on conlict conditions mapping, the application of the Legal - Environmental Criticality Index (ICLA, in Portuguese), the paradigm of Geodiversity and the local sedimentary dynamics. In a Geographic Information System environment, the regionalization of the Environmental Diversity landscape was carried out by "map algebra" of abiotic and biotic information. After identifying and ranking the main conlict conditions by applying the ICLA, each conlict condition with an area over 1,000 m2 was evaluated. There were 71 conlict conditions, which cover 79.91% of the areas occupied with urban or agricultural activities. When comparing the results with the current management instruments, the main restrictions observed were: disrespect for legal and environmental constraints of occupation; poor sanitation; territory and urban zoning incoherent with the socio-spatial dynamics of Jaguaruna; lack of inancial investment; and insuicient technical staf.